"Verdes ideas sin color no pueden dormir furiosamente" (Restricciones que los conceptos [predicados] imponen sobre sus argumentos) - Wilk-Racięska, Joanna (Studia Romanica Posnaniensia, 2004)
The purpose of this paper is a short presentation of some types of restrictions imposed by predicates upon the objects selected as their own arguments. We investigate several grammar procedures used by languages in order to classify objects in argument positions. We will also discuss the relations between these selections and different cultural schemes which can affect the classification and determine the use of linguistic forms. Theoretical instrument applied is the semantic theory known as semantic grammar or semantic syntax.